PENGEMBANGAN PRODUK BERBASIS RUMPUT LAUT BAGI MASYARAKAT DESA PISANGSAMBO KECAMATAN TIRTAJAYA KABUPATEN KARAWANG - Pramono Adi, Catur (Fakultas Pertanian_Universitas Tidar, 2022)
In 2019, the Fishery Product Processing Engineering Study Program of the Karawang Marine and Fisheries Polytechnic has carried out community service activities by applying innovations in processing dodol products made from seaweed, namely carrageenan flour, agar flour and gelatin. The implementation of community service activities was carried out in Pisangsambo Village, Tirtajaya District, Karawang Regency. Pisangsambo Village is one of the centers for producing seaweed (Gracilaria sp.) in Karawang Regency. The purpose of this community service activity is to improve the community's ability to process seaweed so that it can produce products with added value. The First Phase of Community Service Activities in 2020 was carried out in the community of Pisangsambo Village, Tirtajaya District, Karawang Regency on October 1, 2020. The implementation method was carried out through a group-based approach, where all community service activities were carried out using groups as learning media and mentoring, planning, and monitoring and evaluation of all community service activities. The participants in this activity were 25 people, divided into 3 small groups to facilitate mentoring from the lecturer. Each group is given tools and materials to practice the manufacturing method demonstrated by the teacher. Evaluation is carried out orally after the material is given to determine the extent to which participants can absorb the information provided.